2016
DOI: 10.1038/mtna.2016.83
|View full text |Cite
|
Sign up to set email alerts
|

Homology Requirements for Efficient, Footprintless Gene Editing at the CFTR Locus in Human iPSCs with Helper-dependent Adenoviral Vectors

Abstract: Helper-dependent adenoviral vectors mediate high efficiency gene editing in induced pluripotent stem cells without needing a designer nuclease thereby avoiding off-target cleavage. Because of their large cloning capacity of 37 kb, helper-dependent adenoviral vectors with long homology arms are used for gene editing. However, this makes vector construction and recombinant analysis difficult. Conversely, insufficient homology may compromise targeting efficiency. Thus, we investigated the effect of homology lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…These analyses revealed that of the 95 clones analyzed, 85 (89.5%) were correctly targeted, 2 (2.1%) were aberrantly targeted (1 with correct targeting only in the 5′ homology arm and the other with correct targeting only in the 3′ homology arm), and 8 (8.9%) had random vector integration. The Southern blots also revealed the continued presence of the 31 kb band when analyzed with the external 5′ and 3′ probes (Figure 1C), indicating that targeted vector integration had occurred in only one of the two CFTR alleles in all 85 targeted recombinants, a result consistent with our previous study 13 . The frequency of targeting with HD-23.8-CFTRm-PACTk-DTA was not reduced (and perhaps was even a little higher) compared to HD-23.8-CFTR-PACTk, 13 indicating that the twelve 2 bp insertions in the region of homology did not negatively affect targeting efficiency.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These analyses revealed that of the 95 clones analyzed, 85 (89.5%) were correctly targeted, 2 (2.1%) were aberrantly targeted (1 with correct targeting only in the 5′ homology arm and the other with correct targeting only in the 3′ homology arm), and 8 (8.9%) had random vector integration. The Southern blots also revealed the continued presence of the 31 kb band when analyzed with the external 5′ and 3′ probes (Figure 1C), indicating that targeted vector integration had occurred in only one of the two CFTR alleles in all 85 targeted recombinants, a result consistent with our previous study 13 . The frequency of targeting with HD-23.8-CFTRm-PACTk-DTA was not reduced (and perhaps was even a little higher) compared to HD-23.8-CFTR-PACTk, 13 indicating that the twelve 2 bp insertions in the region of homology did not negatively affect targeting efficiency.…”
Section: Resultssupporting
confidence: 90%
“…Altogether, these studies have consistently demonstrated that HDAd-mediated gene editing of iPSCs and ESCs is not associated with ectopic random HDAd integrations, does not affect the undifferentiated state and pluripotency, and maintains genetic and epigenetic integrity. One study found that targeted gene correction in iPSCs by HDAd minimally affects whole-genome mutational load, as determined by whole genome sequencing, 9 and we have demonstrated that footprintless gene editing can be efficiently achieved in human iPSCs with HDAd 13 …”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Basic and clinical investigations are in progress to explore feasibility of innovative genetic and genomic medicine technologies, including transfer of nucleic acids by airway stem/progenitor cells [41,42], zinc finger nuclease-or CRISPR/Cas9-edited human pluripotent stem cells [30,31,32], and nanoparticles [43,44,45], as well as protein replacement via mRNA transfer [46]. Recently, enhanced adenoviral and lentiviral vectors were used to show functional CFTR gene delivery to airways of the CF porcine model [47,48], and the first lentivirus-based clinical trial is scheduled for 2017 [49].…”
Section: Future Directions Relevant To Cf Therapeuticsmentioning
confidence: 99%